Preserving Legal Protection for Sundanese (Sunda Naga and Baduy Kenekes Tribes) Wisdom Amidst Modernization in the Face of COVID-19 Challenges - Suryani, Reni (Yayasan Sinergi Kawula Muda, 2024)
The COVID-19 pandemic has entered various countries around the world, and Indonesia is no exception to this disaster. As a country with diverse cultures, many Indonesians have used local wisdom to face the COVID-19 pandemic. This research aims to understand the government's protection of the Baduy Tribe in Kanekes in facing the COVID-19 pandemic and the existence of the Baduy Tribe in Kanekes in facing the dimensions of modernization and the COVID-19 pandemic. The existence of this indigenous community is regulated in the 1945 Constitution of the Republic of Indonesia Article 18B Paragraph (2). This research uses empirical juridical research, which is a study that examines and analyzes the legal behavior of individuals or the Baduy tribal community in relation to the law. The data sources used are primary data obtained through observation and interviews with informants from the Baduy Tribe and the Sundanese Tribe in Kampung Naga. The results show that they overcome the COVID-19 pandemic through their well-preserved wisdom and culture, forming a strong mentality that allows the existence of life in Kampung Naga and the Baduy Tribe to continue without being affected by COVID-19.